Rule Of Law In The Merdeka Constitution - Khoo, Boo Teong (Journal of Malaysian and Comparative Law, 2000)
This article will look at the original intent of the drafters of the Federal Constitution of Malaysia as reflected in the Reid Commission Report 1957, and as modified in the Government White Paper which formulated the Merdeka Constitution in the creation of an autochthonous Rule of Law for Malaysia Law, including the meaning of the Rule of Law, is never a static phenomenon. This is especially so when there is no clear meaning or content assigned to it by either the Constitution or the legislature of a country.